A dynamic electroviscoelastic problem with thermal effects - SMATA, Sihem; LEBRI, Nemira (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
We consider a mathematical model which describes the dynamic process of contact between a piezoelectric body and an electrically conductive foundation. We model the material’s behavior with a nonlinear electro-viscoelastic constitutive law with thermal effects. Contact is described with the Signorini condition, a version of Coulomb’s law of dry friction. A variational formulation of the model is derived, and the existence of a unique weak solution is proved. The proofs are based on the classical result of nonlinear first order evolution inequalities, the equations with monotone operators, and the fixed point arguments. Mathematics Subject Classification (2010): 74M15, 74M10, 74F05, 49J40.